2021
DOI: 10.3390/atmos12081048
|View full text |Cite
|
Sign up to set email alerts
|

Radon Spatial Variations in University’s Buildings Located in an Italian Karst Region

Abstract: In the framework of a collaboration between INAIL and University of Salento, an indoor radon survey in 54 buildings belonging to the UniSalento University (Southeast Italy) was carried out. The monitored buildings differ by type, construction period, materials, etc., and are located in an area with a morphology characterized mainly by marls, calcareous marls, and calcarenites (karst area). The sample of the survey includes 963 rooms at different floors: it consists in rooms mainly located at ground floor (67%)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 17 publications
1
4
0
Order By: Relevance
“…This hypothesis seems to be supported by both the statistical evidences of the present analysis and the analysis carried out in Leonardi et al [16] on the same dataset. In that study, a very low spatial variability was found: homogenous radon levels were observed among rooms at all floors of 54 buildings, including 4 buildings far from Lecce and excluded in the present analysis.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…This hypothesis seems to be supported by both the statistical evidences of the present analysis and the analysis carried out in Leonardi et al [16] on the same dataset. In that study, a very low spatial variability was found: homogenous radon levels were observed among rooms at all floors of 54 buildings, including 4 buildings far from Lecce and excluded in the present analysis.…”
Section: Discussionsupporting
confidence: 88%
“…A previous paper [16] reported the results of a radon survey carried out in a high number of buildings placed in a small part of an Italian karst area to evaluate the variations of indoor radon concentrations. These buildings present different characteristics in terms of year of construction, materials used, building size, and type of fixtures and heating system.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast with numerous studies of spatial variations in indoor radon, 22,27,34,[48][49][50][51][52][53][54][55][56] usually covering a large number of buildings, it would be much cheaper and less laborious to increase the frequency of data recording, that is, to carry out year-long monitoring by means of CRMs, albeit in a much smaller sample of buildings, given the subject of the study is temporal variations. For example, we assume that in Finland, it would be sufficient to conduct annual monitoring in 30-50 buildings, focusing on the data of Table 3 Table 4 shows how to rationally manage instrumental uncertainty U D using criterion (8).…”
Section: Re Sults and Discussionmentioning
confidence: 99%
“…Perhaps there are consistent patterns in the spatial behavior of radon across different rooms and/or floors in a building that could be statistically justified to enhance the applicability of criterion (1) for the entire building. However, all previously conducted [ 35 , 36 , 37 , 38 ] and planned studies (within the RadoNorm project) of spatial variations of radon within buildings still lack rigorous justification and clear outcomes from the perspective of the actual needs for indoor radon metrology and measurement standardization. Moreover, if the problem of conformity assessment of a room, as an elemental spatial and structural component of a building, remains not fully resolved, then the more comprehensive task of conformity assessment for an entire building solely based on patterns of spatial radon behavior evidently cannot have an effective solution.…”
Section: The Rational Criterion For Conformity Assessmentmentioning
confidence: 99%